Osteochondroma of Mandibular Condyle - Chaurasia, Akhilanand (Journal of Orofacial Research, 2014)
Osteochondroma is one of the most common benign bone tumor of axial skeleton. In oral and maxillofacial region, osteochondroma is rare. This tumor most often involves mandibularcoronoid process however the osteochondroma of mandibular condyle is extremely rare. The anterior and medial half of mandibular condyle is involved more than lateral and superior half. We report a case of osteochondroma of mandibular condyle in 27-year-old female with clinic-radiologic correlation.